Custos da assistência de gestantes hipertensas e seus recém-nascidos - Vidrik, Flávia Cristina Franco [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Introduction: hypertension complicates between 7% and 10% of all pregnancies. Hypertensive disorders determine repeated hospitalizations, longer hospital stays and increased rates of hospitalization in the intensive care unit, which increases hospital costs. It is essential to know the costs of health services to identify the units that need to reduce it, to control spending and eliminate wastes. Objective: To identify and analyze the costs (direct, indirect and total) of assistance provided to hypertensive pregnant women during prenatal care, hospitalization and childbirth. Subjects and Methods: We performed a retrospective, exploratory and quantitative study of pregnant women who received prenatal and delivery care at the Hospital of the Botucatu Medical School - UNESP (HC-FMB-UNESP) in the period of one year (January to December 2011). Costs of 80 patients diagnosed with hypertension and 80 normotensive pregnant women (control group) were analyzed. We used an instrument consisting of two worksheets, in which the data were obtained from medical records and information provided by Cost Center of HC-FMB-UNESP. Results: The indirect, direct and total costs corresponding to prenatal care did not differentiate the groups. On admission there was a significant difference between the control and hypertensive pregnant women when the values of costs (indirect, direct and total) were compared. The value of the total cost of delivery was also significantly higher in the group of hypertensive pregnant women than in the control group. When we analyzed the group of hypertensive pregnant women, stratified according to the clinical manifestation of hypertension, preeclampsia and chronic hypertension superimposed by preeclampsia were both responsible for the higher cost. Conclusion: the total cost of health care for hypertensive pregnant women is greater than that of normotensive pregnant women and among hypertensive women, forms of manifestation ...

Introdução: a hipertensão arterial complica entre 7% e 10% de todas as gestações. As síndromes hipertensivas determinam repetidas internações, maior tempo de internação e aumento das taxas de internação em unidade de cuidados intensivos, o que eleva os custos hospitalares. Ter conhecimento dos custos dos serviços de saúde prestados é essencial para identificar as unidades que precisam reduzi-lo, controlar os gastos e eliminar os desperdícios. Objetivo: identificar e analisar os custos (diretos, indiretos e total) da assistência prestada às gestantes hipertensas durante o pré-natal, a internação e o parto. Sujeitos e métodos: foi realizado estudo retrospectivo, exploratório e quantitativo de gestantes que receberam assistência pré-natal e ao parto no Hospital das Clínicas da Faculdade de Medicina de Botucatu - Unesp (HC-FMB-Unesp)no período de um ano (janeiro a dezembro de 2011). Foram analisados os custos de 80 gestantes com diagnóstico de hipertensão arterial e 80 gestantes normotensas (grupo controle). Utilizou-se um instrumento constituído por duas planilhas, no qual os dados foram obtidos dos prontuários e de informações disponibilizadas pelo Núcleo de Custos do HC-FMB-Unesp. Resultados: os valores dos custos indiretos, diretos e total, correspondentes à assistência pré-natal não diferenciam os grupos estudados. Na internação houve diferença significativa entre os valores dos custos analisados (indireto, direto e total), quando se comparou o grupo controle e o grupo de gestantes hipertensas. O valor do custo total do parto também foi significativamente maior no grupo de gestantes hipertensas quando comparado com o grupo controle. Quando se analisou o grupo de gestantes hipertensas, estratificado segundo a forma de manifestação clínica da hipertensão, as formas pré-eclâmpsia e hipertensão crônica superposta por préeclâmpsia foram responsáveis pelo maior custo. Conclusão: o custo total da...
Keywords: Gravidez - Complicações; Hipertensão na gravidez; Recem-nascidos - Assistência hospitalar; Serviços de saude; Cuidados médicos - Custos; Medical care, Cost of; Hypertension in pregnancy